Analisa Risiko Keselamatan dan Kesehatan Kerja (K3) dengan Menggunakan Metode Hirarc di PT. Otomotif - Maulana, Dede; Insan Waluya, Aris; Suryadi, Suryadi (Dinasti Research, 2024)
Hazard Identification, Risk Assessment, and Control, or HIRARC, is a technique for detecting hazards that is used to calculate risk values and classify them into work-related hazards in order to define the risk control that is applied to each ongoing activity. The purpose of this study is to evaluate and control risks related to occupational safety and health hazards in the charging area of PT. Otomotif. This kind of study combines a descriptive methodology with a qualitative approach. The analysis conducted in the work area of PT. Otomotif's charging area revealed 38 possible dangers, which were categorized into four categories: Low Risk, Medium Risk, High Risk, and Extreme Risk. Controls carried out to reduce the possibility of work accidents include making conveyor bearing covers, making off charge alarms, replacing larger roller materials, adding APD Aprone longan and others.